KEBIASAAN MAKANAN IKAN KRESEK (Thryssa mystax) DI PERAIRAN UJUNG PANGKAH, JAWA TIMUR [Food habit of moustached thryssa (Thryssa mystax) in Ujung Pangkah waters, East Java] - Sulistiono Sulistiono; Nia Triyuniastuti Tirta; Mumiarti Brodjo (Jurnal Iktiologi Indonesia, 2009)
One of an important fishery commodity in Ujung Pangkah waters is moustached thryssa fish. The study aimed to investigate stomach contents of the fish caught in the area. This study was conducted during July to December 2005 in Ujung Pangkah waters, Gresik, East Java using 220 individual of fish samples (n=92 males, n=128 females). Research result shows that shrimps was a basic food, mollusk and parts of crustacean were secondary food, while copepods and pollychaeta were incidental food both for male and female fish. Based on index of stomach contents, the value was higher during July-August and November. Kinds and percentage of the stomach contents varied according to size and time. According to similarity index, stomach contents of male and female fish are similar.